A Study on the Quarterdiurnal Tide in the Thermosphere at Arecibo During the February 2016 Sudden Stratospheric Warming Event. Issue 23 (10th December 2018) - Gong, Yun; Ma, Zheng; Lv, Xiedong; Zhang, Shaodong; Zhou, Qihou; Aponte, Nestor; Sulzer, Michael
Abstract: Using data collected from the Arecibo incoherent scatter radar during 5–10 February 2016, we present a study on the quarterdiurnal tide (QDT) from 250 to 360 km. A sudden stratospheric warming (SSW) event occurred on 8 February coincided with our observation. The maximum amplitude of the QDT, at 37 m/s, is comparable with the diurnal tide and much larger than the semidiurnal tide. The QDT is largely evanescent. Our results manifest that the F region QDT could be as important as the diurnal and semidiurnal tides. The tidal waves show large variability before and after the commencement of the SSW. Our analysis indicates that the enhancement of the QDT is most likely due to the effect of the SSW. Nonlinear interaction of the diurnal tide with the terdiurnal tide is found to play a significant role in amplifying the QDT during the SSW event. Plain Language Summary: We report the first observation and analysis of a strong quarterdiurnal tide in the thermosphere at low latitudes, based on data collected from dual‐beam incoherent scatter radar at Arecibo Observatory. Our study reveals that the quarterdiurnal tide in the thermosphere is just as important as the commonly studied diurnal and semidiurnal tides. According to our analysis, the enhancement of the quarterdiurnal tide in the thermosphere is associated with a sudden stratospheric warming event for the first time. Nonlinear interaction between diurnal and terdiurnal tides is important in enhancing the quarterdiurnal tide. We show that the quarterdiurnal tide is a major contributor to the thermospheric dynamics. The reported results will help modelers to include quarterdiurnal tides into their models to better describe thermospheric dynamics. Key Points: A strong quarterdiurnal tide is first observed at the F region in the low latitudes The enhancement of the QDT is most likely due to the effect of the 2016 SSW The nonlinear interaction between DT and TDT is important in amplifying the QDT during the 2016 SSW